Hierarchy, Coercion, and Exploitation: An Experimental Analysis - Nikos Nikiforakis; Jörg Oechssler; Anwar Shah (University of Heidelberg, Department of Economics, 2012)
The power to coerce workers is important for the efficient operation of hierarchically structured organizations. However, this power can also be used by managers to exploit their subordinates for their own benefit. We examine the relationship between the power to coerce and exploitation in a laboratory experiment where a senior and a junior player interact repeatedly for a finite number of periods. We find that senior players try repeatedly to use their power to exploit junior workers. These attempts are successful only when junior workers have incomplete information about how their effort impacts on the earnings of senior players, but not when they have complete information. Evidence from an incentive-compatible questionnaire indicates that the social acceptability of exploitation depends on whether the junior worker can detect she is being exploited. We also show how a history of exploitation affects future interactions.
urn:nbn:de:bsz:16-opus-134417
Keywords: 330; coercion; exploitation; disobedience; hierarchy; social norms; Personaleinsatzplanung; Unvollkommene Information; Hierarchie; Marxismus; Test